1990
DOI: 10.1007/bf00187330
|View full text |Cite
|
Sign up to set email alerts
|

Photoperiodic requirements for timing onset and duration of the breeding season of the ewe: Synchronization of an endogenous rhythm of reproduction

Abstract: A study was conducted to test the hypothesis that different portions of the annual photoperiodic cycle play different roles in timing the breeding season of the ewe, Ovis aries, an animal in which an endogenous rhythm generates the seasonal reproductive transitions. Adult female sheep were pinealectomized to disrupt transduction of photoperiodic cues at 4 times of the year (summer and winter solstices, vernal and autumnal equinoxes), and the effects on seasonal reproductive neuroendocrine activity were evaluat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
30
0
3

Year Published

1992
1992
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(37 citation statements)
references
References 35 publications
(42 reference statements)
4
30
0
3
Order By: Relevance
“…G(n) values for peak determination were G(l) = 3.8, G(2) = 2.6, G(3) = 1.9, G(4) = 1.5 and G (5) (Restall, 1992). These effects of the ram on the end of the breeding season were evident at a time of year when normal changes in the photoperiod are hypothesized to be relatively unimportant in determining the time of change from the breeding season to the anoestrous state (Wayne et al, 1990 Karsch, 1983) or pinealectomy (Oldham el al, 1979 …”
Section: Introductionmentioning
confidence: 87%
See 1 more Smart Citation
“…G(n) values for peak determination were G(l) = 3.8, G(2) = 2.6, G(3) = 1.9, G(4) = 1.5 and G (5) (Restall, 1992). These effects of the ram on the end of the breeding season were evident at a time of year when normal changes in the photoperiod are hypothesized to be relatively unimportant in determining the time of change from the breeding season to the anoestrous state (Wayne et al, 1990 Karsch, 1983) or pinealectomy (Oldham el al, 1979 …”
Section: Introductionmentioning
confidence: 87%
“…The photoperiod that occurs after the winter solstice has little effect on the duration of the ongoing breeding season (Wayne et al, 1990). This (1990).…”
Section: Introductionmentioning
confidence: 99%
“…Animals in these conditions continue to display cyclical variations in reproductive activity, although not synchronised among animals, and have periods differing synchronisation from 1 year [11]. Particular segments of the annual photoperiodic cycle seem to be more relevant in the synchronisation of endogenous rhythms [12,13]. Thus, the increasing daylength in the spring might be responsible for the onset of the breeding season at the end of the summer, whereas the long, but decreasing daylengths from the summer solstice to the autumnal equinox seem to insure the normal duration of the subsequent reproductive season.…”
Section: Role Of Photoperiod In Reproductive Seasonalitymentioning
confidence: 99%
“…42, No. 1, February 2011, 5-14 which play a critical role in synchronizing the entire rhythm, particularly in relation to the onset of the breeding season in mid-late summer (Malpaux et al 1989;Wayne et al 1990;Woodfill et al 1994). The still long but shortening days experienced after the summer solstice provide the photoperiodic information needed to induce a breeding season of full duration (Malpaux et al 1988;Wayne et al 1990;Woodfill et al 1991) and contribute to maintaining the animal in an active reproductive state (O'Callaghan et al 1991a).…”
Section: Introductionmentioning
confidence: 97%
“…1, February 2011, 5-14 which play a critical role in synchronizing the entire rhythm, particularly in relation to the onset of the breeding season in mid-late summer (Malpaux et al 1989;Wayne et al 1990;Woodfill et al 1994). The still long but shortening days experienced after the summer solstice provide the photoperiodic information needed to induce a breeding season of full duration (Malpaux et al 1988;Wayne et al 1990;Woodfill et al 1991) and contribute to maintaining the animal in an active reproductive state (O'Callaghan et al 1991a). Little, however, is known about the photoperiodic signal provided by the short days around the winter solstice, although Jackson et al (1988) reported that shorter days from the autumnal equinox to the winter solstice serve to break long-day photorefractoriness, which ensures that ewes can respond to the subsequent lengthening days that will synchronize reproductive activity in the next breeding season.…”
Section: Introductionmentioning
confidence: 99%